Prognostic Nutritional Index and the Risk of Mortality in Patients With Acute Heart Failure - Cheng, Yu‐Lun (J Am Heart Assoc, 2017)
BACKGROUND: Nutritional status has been related to clinical outcomes in patients with heart failure. We assessed the association between nutritional status, indexed by prognostic nutritional index (PNI), and survival in patients hospitalized for acute heart failure. METHODS AND RESULTS: A total of 1673 patients (age 76±13 years, 68% men) hospitalized for acute heart failure in a tertiary medical center were analyzed. PNI was calculated as 10×serum albumin (g/dL)+0.005×total lymphocyte count (per mm(3)). National Death Registry was linked to identify the clinical outcomes of all‐cause and cardiovascular death. With increasing tertiles of PNI, age and N‐terminal probrain natriuretic peptide decreased, and body mass index, estimated glomerular filtration rate, and hemoglobin increased. During a mean follow‐up duration of 31.5 months, a higher PNI tertile was related to better survival free from all‐cause and cardiovascular mortality in the total study population and in participants with either reduced or preserved left ventricular ejection fraction. After accounting for age, sex, estimated glomerular filtration rate, left ventricular ejection fraction, serum sodium level, and on‐admission systolic blood pressure, PNI was independently associated with cardiovascular death and total mortality (hazard ratio per 1 SD of the natural logarithm of the PNI: 0.76 [95% CI, 0.66–0.87] and 0.79 [95% CI, 0.73–0.87], respectively). In subgroup analyses stratified by age, sex, left ventricular ejection fraction, body mass index, or estimated glomerular filtration rate, PNI was consistently related to mortality. CONCLUSIONS: PNI is independently associated with long‐term survival in patients hospitalized for acute heart failure with either reduced or preserved left ventricular ejection fraction.